Rumpelstiltskin - "Grimm, Brothers" (MM Publications, 2005)
The fairy tale Rumpelstiltskin originates from German folklore and was popularized by the Brothers Grimm in their 1812 collection Children's and Household Tales. The story revolves around a miller's daughter who is forced to spin straw into gold, a mysterious imp who aids her in exchange for a future reward, and the ultimate revelation of his name as the key to breaking his hold over her child. The name Rumpelstiltskin derives from the German word Rumpelstilzchen, referring to a mischievous spirit from folklore known for causing disturbances. While the tale is primarily associated with German traditions, variations exist across European folklore, such as the English Tom Tit Tot and the Scottish Whuppity Stoorie.
Keywords: European folklore-Fiction: -- Fairy tale